2000
DOI: 10.1023/a:1009290125305
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The centromeric regions and alpha-satellite I sequence were studied on chromosomes 1, 29 and the rob(1;29) translocation in a Portuguese breed of cattle, Barrosa, carrying the translocation. Rob(1;29) centromeric regions showed heterochromatic bands with propidium iodide but, unlike the acrocentric autosomes, no strong centromeric bands were revealed with chromomycin A3. An alpha-satellite I sequence was not found at the centromeres of the X, Y and rob(1;29) chromosomes in the breed, although it was present at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Indeed, a chromosome segment of about 5 Mb translocated from the proximal region of BTA29 to the proximal region of BTA1, with inversion during the evolution of rob(1;29) [224]. A loss of constitutive heterochromatin (C bands) and of some SAT DNA also was observed on rob(1;29) [225,226]. Rob(1;29), first found in Swedish red cattle [1,2], has been found widely in several breeds (more than 50) [227], mainly in meat breeds.…”
Section: Robertsonian Translocations (Rob)mentioning
confidence: 99%
“…Indeed, a chromosome segment of about 5 Mb translocated from the proximal region of BTA29 to the proximal region of BTA1, with inversion during the evolution of rob(1;29) [224]. A loss of constitutive heterochromatin (C bands) and of some SAT DNA also was observed on rob(1;29) [225,226]. Rob(1;29), first found in Swedish red cattle [1,2], has been found widely in several breeds (more than 50) [227], mainly in meat breeds.…”
Section: Robertsonian Translocations (Rob)mentioning
confidence: 99%
“…The dynamic nature of repetitive elements is clearly a basilar reason for genomic plasticity (e.g., [14,102,142,143]) and it is in fact a way of having a low impact on the euchromatic genome [14,97]. Today, an increasing body of evidence strongly validates the involvement of satDNA in the modulation of genomic architectures of a large number of taxa, as in the case of bovids [21,104,144,145], rodents [17,111,143,146], suiformes [57] or genets [147]. This largely extends beyond mammalian evolution, as it can also be observed in insects (e.g., [54,148]), reptiles (e.g., [149]), plants [150] and many other lineages.…”
Section: Modulating Genome Architecture With Satdnasmentioning
confidence: 99%
“…These sequences are essentially centromeric satDNAs, whose detailed physical and organizational analysis contributed much to better comprehend the chromosomal mechanism behind the rob (1;29) translocation [20,145]. In 2000, Chaves and colleagues suggested that this chromosomal abnormality might not be a single event [144] and in 2003, using centromeric satDNA sequences, the same group proposed, for the first time, a two-step mechanism for this rearrangement [20]. This translocation mechanism involved, besides the centric fusion of the two acrocentric chromosomes, the loss and reorganization of specific satDNA families that were retained in the translocated chromosome [20].…”
Section: Remodeling Genome Architecture Through Robertsonian Translocmentioning
confidence: 99%
“…However, as αsatI-5 is present in thousands of copies in all autosomal chromosomes in cattle [30], it is possible that some alpha satellite I repeats are appropriately methylated, while other repeats are more hyper-methylated than the overall proportion of methylation measured here in individual samples suggests. Alternatively, somatic tissue cellular composition may be subtly different in SCNT compared to AI derived fetuses and post-natal animals.…”
Section: Discussionmentioning
confidence: 80%